Design and Development of Portable Mini Water Bamboo Filter - Jamali, Jamalullail; Md Mozasser Rahman (Progress in Engineering Application and Technology, 2022)
Current era globalization, access to clean water is limited. Particularly in rural area due to far away location form cities. Quality of water has become an awareness to population. However, oil and metal mineral resources are non-renewable and depleting. Many effort to reduce the dependency of oil and metal mineral. The research objective is to design and develop a portable mini water bamboo filter that uses activated carbon material as adsorption mechanism removing contaminant from water supply and using a bamboo natural plant stem as main component in canister development. Second objective is to evaluate the quality of developed portable mini water bamboo filter. The scope of study is using bamboo natural product as material and SolidWork 2018 for CAD modelling. Next is to design a friendly environment and biodegradable water filter. The most suitable method is design using Solidwork 2018 Cad modelling software. After fabricating process such as cutting, drilling, and assembling, water is filtered using activated carbon filter layer for quality result. Physical and chemical testing is used for water quality testing method. The result data show activated carbon filter can absorb and filter out most of chemical contaminant. Suggestion for future work is design a finest bamboo mesh for increasing water outlet flow. Further study on bamboo node balanced natural form can be utilized for better water filter inlet design.